PENGARUH SUBSTITUSI STEEL SLAG TERHADAP KUAT TEKAN DAN DAYA SERAP AIR PADA PAVING BLOK - Nur Silvia Arafik (Jurnal Vokasi Teknik Sipil, 2025)
The increase in steel industry activity produces waste that is classified as B3 waste (hazardous, toxic, and odorous), so it has the potential to damage the environment. In accordance with Government Regulation Number 74 of 2001 and Government Regulation Number 18 and 85 of 1999, waste from the steel industry must be managed properly through methods such as thermal processes, stabilization, solidification, and chemical, physical, and biological processing to minimize its impact. The research method used is an experimental method with test objects, namely paving blocks made by replacing some of the fine aggregate with artificial fine aggregate from steel slag. This study used steel slag substitution of 0%, 10%, 15%, and 20% of sand, with the aim of determining the effect on compressive strength, water absorption, and the most optimum proportion of steel slag in paving blocks. The results showed that steel slag substitution of up to 10% increased compressive strength and decreased the absorption capacity of paving blocks, with the best results at a proportion of 10%. Exceeding 10%, compressive strength decreased and absorption capacity increased. So, the optimal proportion of steel slag is 10%.